Identifying Lecturer–Student Interaction and Preference Toward Four English Skills - Soro, Suharyanto H (Jurnal Pendidikan Progresif, 2019)
Identifying lecturer–student interaction and preference toward four english skills. Objectives: The aim of this research was to find out the patterns of classroom interaction and preference toward four English skills for students of Islamic Financial Banking Department. Methods: The data collection procedures in the research were based on classroom participant observation, student interviews, and questionnaire. The language that used for student interviews was English, and sometimes combined with Indonesia language. The last instrument was questionnaire used to know the students’ preference toward four English skills. Findings: The findings of this research indicated that the classroom interaction can be created through mutual understanding and appriciating between lecturer and student, in form of the manner of lecturer’s performance in the classroom, presenting interested and motivated materials, and applying reinforcement. Conclusions: The students’ preference toward four English skills indicated that 61% students liked reading skill very much.Keywords: Lecturer-student interaction, four english skills, interview. DOI: http://dx.doi.org/10.23960/jpp.v9.i2.201904